2021
DOI: 10.3389/feart.2021.698952
|View full text |Cite
|
Sign up to set email alerts
|

Botryoidal and Spherulitic Aragonite in Carbonates Associated with Microbial Mats: Precipitation or Diagenetic Replacement Product?

Abstract: Similar carbonate fabrics may result from different pathways of precipitation and diagenetic replacement. Distinguishing the underlying mechanisms leading to a given carbonate fabric is relevant, both in terms of an environmental and diagenetic interpretation. Prominent among carbonate fabrics are aragonite botryoids and spherulites, typically interpreted as direct seawater precipitates and used as proxies for fluid properties and depositional environments. This study investigated μm to mm-scale Holocene botry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 105 publications
(236 reference statements)
2
7
0
Order By: Relevance
“…The mineralogical composition of the sublittoral bioherms, the focus of this study, does not differ from the bioherms found adjacent to the present‐day shoreline, implying that mineralogy cannot be used to differentiate environments. The predominance of aragonite precipitates associated with calcite and dolomite in GSL microbial bioherms and ooids as reported in this and previous studies (Della Porta, 2015; Dunham et al, 2020; Eardley, 1938; Ge et al, 2021; Pace et al, 2016; Pedone & Folk, 1996; Sandberg, 1975) is explained by the high carbonate supersaturation and Mg/Ca ratio of lake water, which is between 9.6 and 115.7 (cf. Müller et al, 1972).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The mineralogical composition of the sublittoral bioherms, the focus of this study, does not differ from the bioherms found adjacent to the present‐day shoreline, implying that mineralogy cannot be used to differentiate environments. The predominance of aragonite precipitates associated with calcite and dolomite in GSL microbial bioherms and ooids as reported in this and previous studies (Della Porta, 2015; Dunham et al, 2020; Eardley, 1938; Ge et al, 2021; Pace et al, 2016; Pedone & Folk, 1996; Sandberg, 1975) is explained by the high carbonate supersaturation and Mg/Ca ratio of lake water, which is between 9.6 and 115.7 (cf. Müller et al, 1972).…”
Section: Discussionsupporting
confidence: 85%
“…The clotted peloidal and laminated micrite-grade fabric observed petrographically resemble the textures interpreted as microbial boundstone in several studies about recent and fossil microbialites. Nanometrescale sub-spherical carbonate structures eventually coalesce to form larger crystals with rational/euhedral crystal faces as similarly described in studies about microbially mediated carbonate precipitation (Bontognali et al, 2010;Ge et al, 2021;Jones, 2017;Jones & Peng, 2014;Pedley, 2014;Pedley et al, 2009;Perri et al, 2012Perri et al, , 2018. Meldrum and Cölfen (2008) have shown that several biominerals of skeletal organisms can form from amorphous precursors represented by nanoparticles, which are favoured by supersaturation.…”
Section: Microbial Bioherm Fabrics and Precipitation Processesmentioning
confidence: 77%
“…The South Arm sediments (carbonate mud) are composed of dolomite, quartz and calcite with a minor amount of aragonite, albite, illite and poorly crystalline Mg‐bearing clay (Table 2). Stromatolite samples collected from the North Arm and South Arm also consist of predominately aragonite with a trace amount of calcite, which agrees with previous observations (Dunham et al ., 2020; Ge et al ., 2021). Carbonate mud samples collected from ridges between ponds in the North Arm have a similar mineral assemblage as carbonate mud from the South Arm with dolomite, quartz and calcite constituting major components and minor amounts of albite, illite and poorly crystalline Mg‐bearing clay.…”
Section: Resultsmentioning
confidence: 99%
“…The precipitation of disordered dolomite could be triggered by the oversaturation of carbonate in this enclosed region. The spheroidal shape (commonly called spherulite) is very common for carbonate precipitates [38][39][40], which indicates fast precipitation from highly non-equilibrium conditions [41]. The eccentricity of the brown granular core is probably controlled by gravity (relative to the original orientation of the pearl during its formation).…”
Section: Discussionmentioning
confidence: 99%